A Simple Phase Shifting Technique for an Injection Locked Oscillator - Abdul-Niby, M.; Alameen, M.; Baitie, H. (Engineering, Technology & Applied Science Research, 2016)
In Self Oscillating systems, locking of the oscillators can take place for injected signals close in frequency to nth harmonics of the free-running frequency. In this paper, we present a simple design for digital phase shift control by using a harmonically injection locked oscillator (ILO) of 35MHz frequency. Phase shifters at high frequencies are essential in many communication system applications such as frequency synthesis, quadrature signal generation and phase locked loops (PLLs).